Working conditions and health complaints in urban refuse collection: the role of experience - Faria, R.; Sousa, I.C.; Ramos, S. (13th EAOHP Conference, 2018)
The growing attention given to Occupational Health and Safety (OHS) has contributed to the general decline of work accidents in the most part of European countries in last century (Hofmann, Burke, & Zohar, 2017). Despite that, according to Portuguese official data (MTSSS, 2016; Eurostat, 2016), accompanying the economic recovery, we witnessed a slight increase of accidents incidence rate (4.415 in 2013, 4.523 in 2014 and 4.582 in 2015). This corresponds to a total of 5.459.744 (in 2015) lost working days, not considering the lost working days due to work-related diseases. For that reason, OHS is a huge concern for organizations, with strong impacts on costs, productivity or turnover (Malek, El-Safty, El-Safety, & Sorce, 2010); and for workers, in their quality of life (Keogh, Nuwayhid, Gordon, & Gucer, 2000), in their social interaction (Strunin & Boden, 2004), and also in their financial stability (Lawrence, Paustian-Underdahl, & Halbesleben, 2013) and work ability. This proposal describes an action-research, based on a demand from a specific organization (a public company of urban refuse collection and other municipality services) with a high rate of work-related accidents and health complaints, which aims to understand the factors that can explain this situation. Following the theoretical background of work psychology and ergonomics, we designed a mixed method approach centred on workers’ activity (Béguin, 2006; Schwartz, 2005), to investigate the demands, constraints and risk factors that characterize this work situation. The methodology includes documental analysis, observation, individual interviews and a questionnaire, giving special emphasis to the diversity of “ways of doing” the activity among different workers, teams and waste collection modes. Data analysis is currently being conducted, through qualitative (content analysis) and quantitative techniques. Preliminary findings indicate some interesting differences associated with the specific activity of workers – drivers and collectors – showing that it has implications on the type of risk exposure, nature of accidents, and health complaints. Also, results show that workers’ experience seems to influence the way of performing the activity, highlighting the development of health protection strategies over time.